Model of the Independent Learning Campus Internal Quality Assurance System Program based on Artificial Intelligence: Model of the Independent Learning Campus Internal Quality Assurance System Program based on Artificial Intelligence - Zarlis, Muhammad; Elviwani; Dilham, Ami; Buaton, Relita (Yayasan Kita Menulis, 2022)
Research on models of internal quality assurance systems in tertiary institutions online and digitally based on artificial intelligence in supporting the Merdeka Learning Campus Merdeka program in accordance with the cycle of determination, implementation, evaluation, control and improvement. The system is supported by an artificial intelligence approach to determine the implementation and achievement of the Merdeka Learning Campus Merdeka standard and to help universities detect early the impact of the implementation of Merdeka Learning Kampus Merdeka on the development of student competence. The implementation of the Merdeka Learning Campus Merdeka program is recorded in a database with cycles of Determination, Implementation, Evaluation, Control and Improvement to analyze compliance with the establishment, implementation, evaluation, control and improvement of standards for one cycle each year. At the evaluation stage, standard achievement will be produced whether it exceeds, is achieved or deviates to be followed up at the control and improvement stage. With this application, it helps tertiary institutions carry out the standards for the Merdeka Learning Campus Merdeka program standards to be carried out and developed according to the cycle of Determination, Implementation, Evaluation, Control and Improvement